‘Our precious quand même’: French in the Letters of Henry James - Daniel Karlin (Cahiers Victoriens et Edouardiens)
Henry James travelled extensively in France, lived there for months at a time, and was personally acquainted with many leading French writers; he loved and admired the French novel, the French theatre, and the French critical faculty, not to mention ‘the genius of the French language’. His command of French was near-perfect: he was able to write letters in French, and his letters in English are filled with French words and phrases. His creative and critical intelligence was profoundly at work in such word-choices, which are of particular interest in his letters, as opposed to his fiction, where the use of French almost always has a dramatic function. In letters, by contrast, we glimpse James’s own ‘character’ at work—and at play. Patterns of usage may be unconscious (determined by certain recurring epistolary ‘situations’) but there are also cases where the use of French constitutes a trenchant and finely-judged stroke of art. Nowhere is this more so than when the subject is James’s own art. The essay concludes with some examples of this more intense and deliberate practice.